Cloaked By Cyber Space: A Legal Response To The Risks Of Cyber Stalking In Malaysia - Zaiton Hamin; Rosli, Wan Rosalili Wan (Zenodo, 2018)
Cyber stalking generally involves unwarranted, repeated and threatening conduct of the offender via the Internet or social media platforms, which causes fear, distress or alarm to the victim. A qualitative study on the perception of cyber stalking and the adequacy of the anti-stalking law to regulate such crime in Malaysia is somewhat scarce. Hence, this paper seeks to examine cyber stalking risks and the sufficiency of laws to govern such crime and the legal protection afforded to victims. This paper adopts a qualitative methodology, where the data is obtained from eighteen semi-structured interviews conducted with various stakeholders, including the regulators and enforcement officers. Secondary data involves cyber legislation, the Penal Code, and online sources. The findings suggest that cyber stalking risks are often manufactured by the victims, which lead to individual responsibility towards managing and mitigating such risks. The findings have significant implications for lawmakers to either enact specific laws on cyber stalking or amend the Penal Code to include such crime. : {"references": ["Aa, S. (2011). International (cyber) Stalking. In: R. M. Letschert, & J. J. M. van Dijk (Eds.). The new faces of victimhood: globalization, transnational crimes and victim rights (pp. 191-213). Al-Khateeb, H., & Epiphaniou, G. (2016). How technology can mitigate and counteract cyberstalking and online grooming. Computer & Security Journal, 14-18. Bell, J. (1987). Doing Your Research Project \u2013 A Guide for First-Time Researchers in Education and Social Science. Philadelphia: Open University Press. Bertaux, D. (1981). From the Life-History Approach to the Transformation of Sociological Practice. In: Biography and Society: The Life History Approach in the Social Sciences (pp. 29\u201345). London: Sage. Beck, U. (1992).Risk Society: Towards a New Modernity. New Delhi: Sage. (Translated from the German Risikogesellschaft) 1986. Bureau of Justice Statistics (2017). Stalking and Cyberstalking. Office of Justice programs. Retrieved from https://www.bjs.gov/index.cfm?ty=tp&tid=973. Bryman, A. (2007). The Research Question in Social Research: What is the Role? International Journal of Social Research Methodology, 10(1), 5-20. Bocij, P., & Mcfarlane, L. (2002). Online Harassment: Towards a Definition of Cyberstalking. Prison Service Journal, 139, 31-38. Castells, M, & Pekka, H. (2002). The Information Society and the Welfare State: The Finnish Model. Oxford UP: Oxford. Crouch, M., & McKenzie, H. (2006). The Logic of Small Samples in Interview-based Qualitative Research. Social Science Information, 45(4), 483-499. Cybersecurity Malaysia (2010). Cyberstalking a serious Threat. Retrieved from http://cybersecurity.my/en/knowledge_bank/news/2010/main/detail/1853/index.html. Dhillon, G., Challa, C., & Smith, K. (2016). Defining Objectives for Preventing Cyberstalking (pp. 76-87). Presented at the IFIP International Information Security and Privacy Conference. Belgium: Springer International Publishing. Giddens, A. (1999). Risk and Responsibility. Modern Law Review, 62(1), 1-10. Giddens, A. (1990). Consequences of Modernity. Cambridge: Polity Press. Godwin, M. (2013). Cyber Rights: Defending Free Speech in the Digital Age. The MIT Press: Cambridge. Guest, G., Bunce, A., & Johnson, L. (2006). How Many Interviews Are Enough? An Experiment with Data Saturation and Variability. Field Methods, 18(1), 59-82. Hamin, Z., & WanRosli, W. R. (2017). Managing Cyberstalking in Electronic Workplaces, Advance Science Letter, 23(8). Hamin, Z., & Wan Rosli, W. R. (2017). Scent of a Woman: The Gendered Crime of Cyberstalking. Presented at the UUM International Legal Conference (UUM ILC 2017) (Indexed), UUM Sintok, Kedah, Malaysia. Harvey, W. S. (2011). Strategies for Conducting Elite Interviews. Qualitative Research, 11(4), 431-441. Haron, H., & Yusof, F. (2010). Cyberstalking: The Social Impact of Social Networking Technology. Presented at the International Conference on Education and Management Technology (ICEMT 2010). Hazelwood, S. D., & Koon-Magnin, S. (2013). Cyber stalking and cyber harassment legislation in the United States: A qualitative analysis. International Journal of Cyber Criminology, 7(2), 155. Heinrich, P. (2015). Generation iStalk: An Examination of the Prior Relationship between Victim of Stalking and Offenders. Theses, Dissertations and Capstones, Paper 917. Internet World Statistics (2018). Internet Users in the World by Regions. Retrieved from https://www.internetworldstats.com/stats.htm. International Telecommunication Union (2017). ICT Facts and Figures 2017. Retrieved fromhttps://www.itu.int/en/ITU-D/Statistics/Documents/facts/ICTFactsFigures2017.pdf. Jaishankar, K. (2011). Cyber Criminology: Exploring Internet Crimes and Criminal Behaviour. Florida: Taylor & Francis Group. Jesson, J., Matheson, L., Lacey, F. M. (2011). Doing Your Literature Review: Traditional and Systematic Techniques. Cambridge: Sage. p. 9. Knight, M. (2015). Stalking and Cyberstalking in the United States and Rural South Dakota: Twenty-Four Years after the First Legislation. South Dakota Law Review, 59 S.D.L.REV.392. Lamplugh, D., & Infield, P. (2003). Harmonising Anti-Stalking Laws. The George Washington International Law Review, 34, 853. Leong, L., & Morando, J. (2015). Communication in Cyberspace. University of Denver Sturm College of Law, Legal Research Paper Series. Working Paper No. 15-11. Logan, T. (2010). Research on partner stalking: Putting the pieces together. Lexington, KY: University of Kentucky, Department of Behavioural Science & Centre on Drug and Alcohol Research. National Institute of Justice. MCMC (2017). Internet Users Survey 2017. Retrieved from https://www.mcmc.gov.my/skmmgovmy/media/General/pdf/MCMC-Internet-Users-Survey-2017.pdf. McNamara, C. L., & Marsil, D. (2012). The prevalence of stalking among college students: The disparity between researcher-and self-identified victimization. Journal of American College Health, 60(2), 168-174. Medlin, A. N. (2002). Stalking to Cyberstalking, a Problem Caused by the Internet. Law and the Internet, Fall 2002 papers, Georgia State University College of Law, 140 Decatur St., Atlanta, Georgia 30303 http://gsulaw.gsu.edu/lawand/papers/fa02/medlin. Meloy, J. (1998). The Psychology of Stalking. The Psychology of Stalking: Clinical and Forensic Perspectives. London: Academic Press. Mullen, P., Path\u00e9, M., Purcell, R. (2000). Stalkers and their victims. Cambridge: Cambridge University Press. Mutawa, N., Bryce, J., Fanqueira, V., & Marrington, A. (2016). Forensic Investigation of Cyberstalking Cases Using Behavioural Evidence Analysis. Digital Investigation, 16, 96-103. Ngo, F. (2014). Toward a Comprehensive Model on Stalking Acknowledgement: A Test of Four Models. Crime & Delinquency, 60(8), 1158-1182. Nobles, M. R., Reyns, B. W., Fox, K. A., Fisher, B. S. (2014). Protection against Pursuit: A Conceptual and Empirical Comparison of Cyberstalking and Stalking Victimization among a National Sample. Justice Quarterly, 31(6), 986-1014. Norden, S. (2013). How the Internet has Changed the Face of Crime. Masters of Science Thesis (unpublished). Paladin. (2016). Stalking and Harassment \u2013 A Shorthand Guide about Digital and Cyberstalking. Retrieved from http://paladinservice.co.uk/wpcontent/uploads/2014/11/Digital-and-Cyber-Stalking-Toolkit.pdf. Patel, P. (2013). Rebalancing the Scale: Prioritizing Victims of Crime in the Criminal Justice System. Retrieved from http://www.roadpeace.org/resources/REBALANCING_THE_SCALES.pdf. Parsons, T. (1961). Theories of Society; Foundations of Modern Sociological Theory. Illinois: The Free Press of Glencoe. Perry, J. (2012). Digital Stalking: A Guide to Technology Risks for Victims. Retrieved from www.digital-stalking.com. Piotrowski, C. (2012). From Workplace Bullying to Cyberbullying: The Enigma of E-Harassment in Modern Organizations. Organization Development Journal, 3(4). Pittaro, M. L. (2007). Cyberstalking: An Analysis of Online Harassment and Intimidation. International Journal of Cyber Criminology, 1(2), 180\u2013197. Reyns, B. W., Henson, B. (2015). The Thief with a Thousand Faces and the Victim with None: Identifying Determinants for Online Identity Theft Victimization with Routine Activity Theory. International Journal of Offender Therapy and Comparative Criminology, 1-21. Scheibelhofer, E. (2008). Combining Narration \u2013 Based Interviews with Topical Interviews: Methodological Reflections on Research Practices. International Journal of Social Research Methodology, 11(5), 403-416. p. 405. Sheridan, L., & Grant, T. (2007). Is Cyberstalking Different? Psychology, Crime & Law, 13(6), 627-640. Seidman, I. (2006). Interviewing as Qualitative Research. New York: Teachers College Press. Smoker, M., & March, E. (2017). Predicting perpetration of intimate partner cyberstalking: Gender and the Dark Tetrad, Computers in Human Behaviour, 72, 390-396. Silverman, D. (2013). Doing Qualitative Research. Los Angeles: SAGE. Spence-Diehl, E. (2003). Stalking and Technology: The Double-Edged Sword. Journal of Technology in Human Services, 22(1), 5-18. Spitzberg, B. H., & Cupach, W. R. (2007). The State of The Art of Stalking: Taking Stock of the Emerging Literature. Aggression and Violent Behaviour, 12, 64-86. Tavani, H., & Grodzinsky, F. (2002). Cyberstalking, Personal Privacy and Moral Responsibility. Ethics and Information Technology, 4, 123. Tokunaga, R. S., & Aune, K. (2015). Cyber-Defence: A Taxonomy of Tactics for Managing Cyberstalking. Journal of Interpersonal Violence, 1-25. Thomas, K. R. (1993). How to Stop the Stalker: State Anti- Stalking Laws. Criminal Law Bulletin, 29(2), 124-136. Wall, D.S. (2005) The Internet as a conduit for criminals. In A. Pattavina (Ed.) Information \tTechnology and the Criminal Justice System, 77-98. Thousand Oaks, CA: Sage."]}